A Zero-dissipative Runge-Kutta-Nyström Method with Minimal Phase-lag for Oscillatory Problems - Senu, Norazak; Suleiman, Mohamed; Ismail, Fudziah; Othman, Mohamed (2009)
A three-stage third-order explicit Runge-Kutta-Nyström method is developed to integrate second-order differential equations of the form where the solution is oscillatory. Presented are formula which has zero-dissipation, maximum order of dispersion (or minimal phase-lag) and at the same time with ’small’ principal local truncation error terms . The interval of periodicity is investigated and calculated. Numerical comparisons with current methods in the literature show its clear advantage in term of accuracy.